High Gain Multistage Power Amplifier for Internet of Things (IoT) Applications. - Krishnarajoo, Selvarajah; Mariappan, Selvakumar; Rajendran, Jagadheswaran; Mohd Noh, Norlaili; ., . (International Journal of Engineering and Technology, 2018)
This paper presents the design of a linear power amplifier (PA) with high gain and low power consumption for Internet of Things (IOT) application. The gain of the PA is boosted with driver stage integration. The effect of Cgs capacitance is mitigated by utilizing a passive linearizer, which improves the efficiency and linearity of the PA while delivering gain of 19dB from 2.4GHz to 2.5GHz. The designed PA exhibits gain of 19.6dB with PAE of 29.71% at maximum output power of 15.9dBm. The corresponding OIP3 is 21dBm at drain voltage of 18.V. Â The designed multistage PA with passive linearizer acts as a method to improve linearity and gain of the 180nm CMOS power amplifier without trading-off the efficiency and maximum output power at the operating frequency.Â Â